2018
DOI: 10.1186/s12916-018-1075-x
|View full text |Cite
|
Sign up to set email alerts
|

Four-year effects of exercise on fatigue and physical activity in patients with cancer

Abstract: BackgroundIn the earlier randomized controlled Physical Activity during Cancer Treatment (PACT) study, we found beneficial effects of an 18-week supervised exercise program on fatigue in patients with newly diagnosed breast or colon cancer undergoing adjuvant treatment. The present study assessed long-term effects of the exercise program on levels of fatigue and physical activity 4 years after participation in the PACT study.MethodsThe original study was a two-armed, multicenter randomized controlled trial com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 24 publications
3
87
3
1
Order By: Relevance
“…In other words, there were no consistent effects of the different exercise doses and types during breast cancer chemotherapy on patient-reported outcomes at all three follow-up time points. This null finding is in contrast to previous studies 5,9,10,[34][35][36] which have reported positive longer-term effects of exercise performed during breast cancer chemotherapy; however, these studies have compared an exercise intervention to no exercise, unlike that the CARE Trial that compared three different exercise interventions. One possible explanation for the null finding concerning the three different exercise prescriptions tested in the CARE Trial is that the differences in the exercise prescriptions were modest and only produced small differences in outcomes even at the immediate postintervention time point.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…In other words, there were no consistent effects of the different exercise doses and types during breast cancer chemotherapy on patient-reported outcomes at all three follow-up time points. This null finding is in contrast to previous studies 5,9,10,[34][35][36] which have reported positive longer-term effects of exercise performed during breast cancer chemotherapy; however, these studies have compared an exercise intervention to no exercise, unlike that the CARE Trial that compared three different exercise interventions. One possible explanation for the null finding concerning the three different exercise prescriptions tested in the CARE Trial is that the differences in the exercise prescriptions were modest and only produced small differences in outcomes even at the immediate postintervention time point.…”
Section: Discussioncontrasting
confidence: 91%
“…In other words, there were no consistent effects of the different exercise doses and types during breast cancer chemotherapy on patient‐reported outcomes at all three follow‐up time points. This null finding is in contrast to previous studies which have reported positive longer‐term effects of exercise performed during breast cancer chemotherapy; however, these studies have compared an exercise intervention to no exercise, unlike that the CARE Trial that compared three different exercise interventions.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Unfortunately, many of the benefits of exercise during breast cancer chemotherapy dissipate quickly after cessation of the exercise program. Some studies have shown diminished effects as early as 6 months postintervention [5,[8][9][10] and few trials have even reported longer-term effects beyond 6 months [11][12][13][14]. We recently reported the 6-, 12-, and 24month follow-up of the Combined Aerobic and Resistance Exercise (CARE) Trial which compared different types and doses of exercise during breast cancer chemotherapy [15].…”
Section: Introductionmentioning
confidence: 99%